Conceptualizing the integration of HIV treatment and prevention: findings from a process evaluation of a community-based, national capacity-building intervention. - Mykhalovskiy, Eric; Patten, San; Sanders, Chris; Bailey, Michael; Taylor, Darien (International journal of public health, 2009)
This paper responds to a gap in knowledge about the conceptualization of integration in community-based AIDS organizations (CBAOs).
Keywords: Anti-HIV Agents; Canada; Community Health Services; Comprehensive Health Care; Cooperative Behavior; Cross-Cultural Comparison; Cross-Sectional Studies; Delivery of Health Care, Integrated; Disease Outbreaks; Health Education; Health Promotion; Health Services Research; HIV Infections; Humans; Information Services; Inservice Training; Needs Assessment; Primary Prevention; Process Assessment (Health Care)